Indonesia Economic Quarterly, June 2017 : Upgraded - World Bank (World Bank, Washington, DC, 2018)
The Indonesia Economic Quarterly (IEQ) has two main aims. First, it reports on the key developments over the past three months in Indonesia’s economy, and places these in a longerterm and global context. Based on these developments, and on policy changes over the period, the IEQ regularly updates the outlook for Indonesia’s economy and social welfare. Second, the IEQ provides a more in-depth examination of selected economic and policy issues, and analysis of Indonesia’s medium-term development challenges. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia’s evolving economy.